Immune Dysregulation Mimicking Systemic Lupus Erythematosus in a Patient With Lysinuric Protein Intolerance: Case Report and Review of the Literature - Contreras, Josefina Longeri; Ladino, Mabel A.; Aránguiz, Katherine; Mendez, Gonzalo P.; Coban-Akdemir, Zeynep; Yuan, Bo; Gibbs, Richard A.; Burrage, Lindsay C.; Lupski, James R.; Chinn, Ivan K.; Vogel, Tiphanie P.; Orange, Jordan S.; et al. (Frontiers in Pediatrics, 2021)
Lysinuric protein intolerance (LPI) is an inborn error of metabolism caused by defective transport of cationic amino acids in epithelial cells of intestines, kidneys and other tissues as well as non-epithelial cells including macrophages. LPI is caused by biallelic, pathogenic variants in SLC7A7. The clinical phenotype of LPI includes failure to thrive and multi-system disease including hematologic, neurologic, pulmonary and renal manifestations. Individual presentations are extremely variable, often leading to misdiagnosis or delayed diagnosis. Here we describe a patient that clinically presented with immune dysregulation in the setting of early-onset systemic lupus erythematosus (SLE), including renal involvement, in whom an LPI diagnosis was suspected post-mortem based on exome sequencing analysis. A review of the literature was performed to provide an overview of the clinical spectrum and immune mechanisms involved in this disease. The precise mechanism by which ineffective amino acid transport triggers systemic inflammatory features is not yet understood. However, LPI should be considered in the differential diagnosis of early-onset SLE, particularly in the absence of response to immunosuppressive therapy.